HIV stadium IV on ARV, Tuberculosis Paru dan Gizi Buruk Tipe Marasmus pada Anak Perempuan 10 tahun: Laporan Kasus - Anniza Agustina; Kinanti Rahmadita; Shinta Nareswari (Medula, 2022)
Human Immunodeficiency Virus (HIV) infection remains a global problem, with nearly 38 million people infected worldwide. Tuberculosis (TB) is the most common opportunistic infection found in HIV patients. Malnutrition in children with HIV infection can be caused by various factors such as individual factors, namely the absorption and metabolism disorders of children. Reported a 10-year-old girl with complaints of fever, cough and weight loss. The patient has been diagnosed with HIV since 4 years ago. The HIV status of both parents is unknown. History of contact with adult TB, namely the patient's father. Physical examination found multiple submental and submandibular lymph nodes (KGB) measuring 1x1cm palpable soft. On auscultation of the lungs there were crackles in both lung fields. Nutritional status of malnourished patients with marasmus type. AP chest x-ray examination revealed a primary impression of TB. The medical therapy given was continuing antiretroviral drugs (tenofovir, lamivudine, and evapirenz), D5¼NS fluids 1200cc/day, antibiotics ceftriaxone 1.2g/24 hours, antipyretic paracetamol syrup 3x7.5ml, folic acid 1x5mg on the first day and 1x1mg on the next day, Vitamin C 2x50mg, vitamin B complex 1 tablet per day and salbutamol 3x1,5mg. Pulmonary TB was treated with rifampin 200 mg/day, isoniazid 140 mg/day, ethambutol 300 mg/day, and pyrazinamide 500 mg/day. Non-medical therapy in the form of oral nutrition, namely rice, side dishes, and milk with a total calorie of 55kcal/kgBW/day.